Cavitation erosion of glass fibre reinforced polymer composites with unidirectional layup. (15th November 2019) - Guobys, R.; Rodríguez, Á.; Chernin, L.
Abstract: Glass fibre reinforced polymer (GFRP) composites are increasingly used in marine applications and can be subjected to aggressive environmental effects, one of which is cavitation. This study investigates the behaviour of unidirectional GFRP composites exposed to cavitation erosion generated using an ultrasonic transducer. Cavitation erosion tests were performed in accordance with the ASTM G32 standard. All specimens were preconditioned to eliminate the influence of water absorption on the mass loss caused by cavitation. The erosion process was monitored with a microscope and the mass loss was measured at regular periods. The tested specimens were scanned with X-ray computed microtomography. The research findings indicated that the erosion process was affected by several parameters including specimen thickness, distance between fibre bundles, bundle shape and distribution. The initiation and development of erosion damage were highly influenced by the surface condition. Cavitation erosion traced parts of fibre bundles located closer to the surface creating trenches and valleys on the surface. The regions with thick epoxy layers above and between fibre bundles were much less susceptible to erosion damage. Several erosion mechanisms were identified and discussed. The research findings also highlighted the difficulties in characterising ultrasonic cavitation erosion of GFRP composites using acoustic impedance and mean erosion depth. Highlights: Preconditioning of GFRP specimens and experimental setup influence erosion results. Fibre/epoxy distribution affects composite resistance to cavitation erosion. Surface roughness leads to cavitation erosion localisation. Specimen thickness affects the ultrasonic erosion process. Maximum erosion depth is much greater than the mean erosion depth.